Segmental Timber Plate Shell for the Landesgartenschau Exhibition Hall in Schwäbisch Gmünd—the Application of Finger Joints in Plate Structures. Issue 2 (June 2015) - Li, Jian-Min; Knippers, Jan
Segmental plate shells are an interesting option for the design and construction of cost-effective shell structures. They are composed of prefabricated segmental plates that are joined together to become an integral structure that generates a shell action and transfers external loads into membrane forces. However, connections between segmental plates nearly always weaken shell structures as they disturb the material continuity and thus their stiffness. The application of finger joint connections can effectively increase the in-plane stiffness and thus makes plate shell structures stiffer and stronger. Moreover, they attract more forces to flow through the connection in the form of in-plane shears instead of axial forces and thus reduce the load in the axial direction of a connection. As a result, the application of finger joints allows a lighter axial joint design with smaller screw diameters, which is preferred in a thin timber plate structure. The paper presents the Landesgartenschau Exhibition Hall as a successful demonstrator for segmental timber plate shells and highlights the design of the finger joint connections.